Employee Productivity in View of Work Environment and Work Culture in the Digital Era Case Study of Elementary School Educators - Seviana Nadia Triadi; Syahrul Nafizul Hafiz; Anna Suzana (Dinasti International Journal of Education Management And Social Science, 2025)
The purpose is to examine how employee productivity in the digital age is impacted by workplace culture and surroundings. The workplace has changed significantly as a result of the quick advancement of technology, making it more crucial than ever to comprehend the elements that influence worker performance. A comfortable and productive workplace is influenced by a number of factors, including sufficient amenities and technology assistance. In addition, a positive work culture, which reflects the values of collaboration, innovation, and strong work ethics, also boosts employee motivation to achieve optimal performance. The digital era presents new challenges and opportunities, such as work flexibility and virtual communication, which require employees to adapt to the existing dynamics. The results show that the synergy between a good work environment and a supportive work culture can significantly increase employee productivity. This is expected to be a reference for employees in designing strategies to increase work productivity in the midst of changes in the evolving world of work.